Diagnosis Change in Voice-Disordered Patients Evaluated by Primary Care and/or Otolaryngology: A Longitudinal Study. (January 2014) - Cohen, Seth M.; Dinan, Michaela A.; Roy, Nelson; Kim, Jaewhan; Courey, Mark
Objective: Accurate diagnosis of a voice disorder is an essential first step toward its appropriate treatment. We examined differences in laryngeal diagnosis over time in outpatients evaluated by primary care physicians (PCPs) and/or otolaryngologists. Study Design and Setting: Retrospective analysis of data from a large, national administrative US claims database. Subjects and Methods: Patients with laryngeal disorders based on International Classification of Diseases, Ninth Revision, Clinical Modification codes from January 1, 2004, to December 31, 2008, with at least 2 outpatient visits by a PCP and/or otolaryngologist and continuously enrolled for 12 months were included. The initial and final laryngeal diagnoses were tabulated. Results: Of approximately 55 million individuals, 29, 501 met inclusion criteria. More than half the patients in the PCP to otolaryngology group and one-third of the otolaryngology to otolaryngology group had different laryngeal diagnoses over time. Three-fourths of patients with an initial acute laryngitis diagnosis in the PCP to otolaryngology group and half of the otolaryngology to otolaryngology group had a different final laryngeal diagnosis. Of patients with a final laryngeal cancer diagnosis, one-fourth of the otolaryngology to otolaryngology group had an initial diagnosis of nonspecific dysphonia, and one-fifth of the PCP to otolaryngology group had an initial diagnosis of acute laryngitis. Conclusion: Differential diagnosis of voice disorders often evolves over time. The impact on treatment and health care utilization are important areas of future study.